2019
DOI: 10.2188/jea.je20180011
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Alcohol Consumption, and Risks for Biliary Tract Cancer and Intrahepatic Bile Duct Cancer

Abstract: Background: Smoking and alcohol are established risk factors for several types of cancer, but the effects on biliary cancers, comprising biliary tract cancer (BTC) and intrahepatic bile duct cancer (IHBDC), have been inconclusive. Methods: In this population-based prospective cohort study in Japan, we investigated the association of smoking and alcohol consumption with the risks of BTC and its subtypes and IHBDC incidence in men and women. Furthermore, the association of smoking stratified by drinking status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Thus, 20 original articles were included in the present meta‐analysis. Supplementary Tables S2 and S3 summarize the main characteristics of these case–control ( n = 11) and cohort studies ( n = 9) . The original articles were published between 1990 and 2019, and were based on 4,676 gallbladder cancer cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, 20 original articles were included in the present meta‐analysis. Supplementary Tables S2 and S3 summarize the main characteristics of these case–control ( n = 11) and cohort studies ( n = 9) . The original articles were published between 1990 and 2019, and were based on 4,676 gallbladder cancer cases.…”
Section: Resultsmentioning
confidence: 99%
“…The original articles were published between 1990 and 2019, and were based on 4,676 gallbladder cancer cases. In all, 10 studies provided a measure of association (or provided information to derive it) for current smokers, 9 for former smokers and 18 for ever smokers, compared to never smokers. Four studies reported RRs for smoking intensity and three for smoking duration for current smokers, and one study reported RRs for time since quitting for former smokers…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…100 Another prospective cohort study in Japan reported a HR = 1.96 (95% CI 0.99-3.91) for iCCA in regular drinkers consuming ≥300 g/day of ethanol, compared to non-drinkers; however, these results did not reach statistical significance (P-trend = 0.065), probably because of the small number of iCCA cases included. 101 Whether the association between alcohol consumption and iCCA is related to liver disease (i.e. alcoholic liver disease and cirrhosis), or to other underlying carcinogenic mechanisms is unclear.…”
Section: Alcohol Consumptionmentioning
confidence: 99%